A constitutive thiamine metabolism mutation, thi80, causing reduced thiamine pyrophosphokinase activity in Saccharomyces cerevisiae. - Nishimura, H (1991)
We identified a strain carrying a recessive constitutive mutation (thi80-1) with an altered thiamine transport system, thiamine-repressible acid phosphatase, and several enzymes of thiamine synthesis from 2-methyl-4-amino-5-hydroxymethylpyrimidine and 4-methyl-5-beta-hydroxyethylthiazole. The mutant shows markedly reduced activity of thiamine pyrophosphokinase (EC 2.7.6.2) and high resistance to oxythiamine, a thiamine antagonist whose potency depends on thiamine pyrophosphokinase activity. The intracellular thiamine pyrophosphate content of the mutant cells grown with exogenous thiamine (2 x 10(-7) M) was found to be about half that of the wild-type strain under the same conditions. These results suggest that the utilization and synthesis of thiamine in Saccharomyces cerevisiae is controlled negatively by the intracellular thiamine pyrophosphate level.